We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
75
1
avatar

The explicit rule for a sequence is given. 

 

\(a_n\)= 1/2(4/3)^n-1

 

Enter the recursive rule for the geometric sequence.

 

\(a_1\)=_______ ;     \(a_n\)=________

 

Thanks so much!

 Mar 4, 2019
 #1
avatar+101856 
+1

a1 =  (1/2)(4/3)^(1 - 1)   = (1/2) (4/3)^0 = (1/2)(1)  = 1/2

 

an = an-1 (4/3)

 

cool cool cool

 Mar 4, 2019

3 Online Users